The 3'-terminal end (NCCA) of tRNA determines the structure and stability of the aminoacyl acceptor stem. - Limmer, S (1993)
We have done a systematic study on the contribution of the single-stranded NCCA end (where N is any nucleotide) to the stability of the aminoacyl stem of tRNA. A 7-bp RNA duplex with the single-strand ACCA 3' terminus derived from the aminoacyl stem of Escherichia coli tRNA(Ala) and several chemically synthesized sequence variants are characterized by proton NMR and thermodynamic parameters. The single-stranded 3' terminus noticeably stabilizes the duplex in a sequence-dependent manner. Though the largest contribution to the stability gain due to the ACCA end is provided by the first dangling 3' nucleotide, the influence of even the fourth nucleotide is measurable. The nature of the N73 discriminator base influences the stem structure and stability, which may be important for the recognition of tRNA by aminoacyl-tRNA synthetase. The stepwise attachment of the nucleotides to the 3' tail improves the stacking of the unpaired bases over the helix stem. Hence, the ACCA end appears to be structured. Replacing Mg2+ with Mn2+ causes broadening of certain imino proton peaks in the NMR spectrum, indicating a specific divalent metal ion binding site in the vicinity of the major identity element of the duplex (G3-U70) that is required for its recognition by the Ala-tRNA synthetase.